Extramedullary multiple myeloma patient-derived orthotopic xenograft with a highly altered genome: combined molecular and therapeutic studies - Lourdes Farre; Gabriela Sanz; Neus Ruiz-Xivillé; Manuel Castro de Moura; Juan Francisco Martin-Tejera; Samuel Gonçalves-Ribeiro; Maria Martinez-Iniesta; Monica Calaf; Jose Luis Mosquera; José Ignacio Martín-Subero; Isabel Granada; Manel Esteller; et al. (The Company of Biologists, 2021)
Extramedullary multiple myeloma (EMM) has an overall survival of 6 months and occurs in 20% of multiple myeloma (MM) patients. Genetic and epigenetic mechanisms involved in EMM and the therapeutic role of new agents for MM are not well established. Besides, well-characterized preclinical models for EMM are not available. Herein, a patient-derived orthotopic xenograft (PDOX) was generated from a patient with an aggressive EMM to study in-depth genetic and epigenetic events, and drug responses related to extramedullary disease. A fresh punch of an extramedullary cutaneous lesion was orthotopically implanted in NOD.Cg-PrkdcscidIl2rgtm1Wjl/SzJ(NSG) mouse. The PDOX mimicked histologic and phenotypic features of the tumor of the patient. Cytogenetic studies revealed a hyperploid genome with multiple genetic poor-prognosis alterations. Copy number alterations (CNAs) were detected in all chromosomes. The IGH translocation t(14;16)(q32;q23)IGH/MAF was already observed at the medullary stage and a new one, t(10;14)(p?11-12;q32), was observed only with extramedullary disease and could be eventually related to EMM progression in this case. Exome sequencing showed 24 high impact single nucleotide variants and 180 indels. From the genes involved, only TP53 was previously described as a driver in MM. A rather balanced proportion of hyper/hypomethylated sites different to previously reported widespread hypomethylation in MM was also observed. Treatment with lenalidomide, dexamethasone and carfilzomib showed a tumor weight reduction of 90% versus non-treated tumors, whereas treatment with the anti-CD38 antibody daratumumab showed a reduction of 46%. The generation of PDOX from a small EMM biopsy allowed us to investigate in depth the molecular events associated with extramedullary disease in combination with drug testing.